2015
DOI: 10.1039/c5ra08270f
|View full text |Cite
|
Sign up to set email alerts
|

Significant roughness enhancement of fluorine-doped tin oxide films with low resistivity and high transparency by using HNO3 addition

Abstract: Current development of fluorine-doped tin oxide (FTO) films for application in solar cells is limited by tradeoffs among surface roughness related light trapping, optical transparency and electrical conductivity. Proposed methods for improving the surface roughness are usually dependent upon thickness increment or sacrificing the conductivity. In this study, we report a simple method for preparing FTO films with a flower-like grain morphology and thus a higher than ever mean roughness of 51.4-73.3 nm or mean-r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 34 publications
0
5
0
Order By: Relevance
“…The amount of F- dopant precursor is the same for this set of samples, so changes in p are assumed to be due to the change in translation rate and hence growth rate. The reduced growth rate results in decreased TC along the (200) preferred orientation and an increase in the (110) direction [22,23]. A reduction in (200) orientation has previously been linked by Wang et al [22] to lower conductivities.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The amount of F- dopant precursor is the same for this set of samples, so changes in p are assumed to be due to the change in translation rate and hence growth rate. The reduced growth rate results in decreased TC along the (200) preferred orientation and an increase in the (110) direction [22,23]. A reduction in (200) orientation has previously been linked by Wang et al [22] to lower conductivities.…”
Section: Resultsmentioning
confidence: 99%
“…Due to limited supply of polar by-product molecules in S4-S6, fewer molecules are absorbed on the F-(101) planes and result in a moderately stronger (110) peak. In a recent study, Wang and co-workers showed that different preferred orientations of FTO films (deposited by APCVD) could be achieved using different additives and then how their properties are consequently altered [23]. It was clearly demonstrated that the films with a preferred orientation along the (200) axis are highly desired as they yield improved electrical conductivities [24].…”
Section: Resultsmentioning
confidence: 99%
“…The average RMS roughness value of the BVO3 film was lower than the BVO5 film, indicating higher surface roughness in the thin film, which may influence the optical transmittance and electrical transport properties ( Figure ). [ 45 ]…”
Section: Resultsmentioning
confidence: 99%
“…[68][69][70] A rough surface predominantly enhances the reflection of incident photons back into the electrode, thereby decreasing the loss of photons and aiding the improvement in light gathering ability. 16,71 3.4. Photoluminescence measurements Fig.…”
Section: Surface Morphology Contact Angle Measurement and Chemical Co...mentioning
confidence: 99%